Novel Nanoarchitectures Based on Lignin Nanoparticles for Electrochemical Eco‐Friendly Biosensing Development - Tasca-Gottardo, F; Tasca-Gottardo, F (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Novel nanoarchitectures based on lignin nanoparticles (LNPs) were designed and realized for electrochemical eco‐friendly biosensing development. Two types of lignin nanoparticles were utilized for the modification of a gold bare electrode, namely organosolv (OLNPs) and kraft lignin (KLNPs) nanoparticles, synthetized from a sulfur‐free and a sulfur lignin, respectively. The electrochemical behavior of LNP‐modified electrodes was studied using two electrochemical techniques, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Compared to the gold bare electrode, an evident decrease in the faradaic current and increase of the ΔEp were observed in cyclic voltammograms. In addition, larger semicircles were registered in Nyquist plots. These results suggest a strong inhibition effect of the electron transfer reaction by LNPs layer, especially in the case of KLNPs. The modified electrodes, properly assembled with concanavalin A (ConA) and glucose oxidase (GOx), were successively tested as biosensing platforms for glucose, showing a sensitivity of (4.53 ± 0.467) and (13.74 ± 1.84) μA mM−1 cm2 for Au/SAMCys/OLNPs/ConA/GOx and Au/KLNPs/ConA/GOx biosensors, respectively. Finally, different layers of the KNLPs/ConA/GOx‐modified Au electrode were tested, and the three‐layered Au(KNLPs/ConA/GOx)3 showed the best analytical performance. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.